Energy Optimization of Ethylenediamine Production Process Using Pinch Technology - Najwa Putri Indira Kusuma; Maeza Dhenta Purniawan; Zahwa Sabilla Sulistyaningdyah; Salma Syifa Mu’minah (Vocational College of Universitas Diponegoro, 2025)
This study presents a comprehensive energy optimization analysis of the ethylenediamine (EDA) production process using Pinch Technology methodology. EDA is a critical chemical compound widely utilized in pharmaceuticals, agrochemicals, polymers, and chelating agents, with its conventional production process being inherently energy-intensive. The research employs HINT (Heat Integration) software to systematically evaluate energy consumption patterns, identify heat recovery opportunities, and design an optimal heat exchanger network for the EDA production system. The production process involves the catalytic reaction between monoethanolamine (MEA) and ammonia at 235 °C and 30 atm, followed by multiple separation and purification stages. Through pinch analysis, process streams were identified and evaluated, revealing significant opportunities for internal heat recovery. The baseline system without integration showed heating requirements of 734.546 kW and cooling requirements of 734.546 kW, totaling 1,469.092 kW of external utility consumption. The analysis determined minimum energy requirements of 439.578 kW for heating and 0.0 kW for cooling utilities, with a pinch temperature of 245 K at ΔTmin of 10 K. The optimized heat exchanger network, comprising eight heat exchangers with a hierarchical configuration (H1: 55.433 kW, H2: 349.878 kW, H3: 102.454 kW, H8: 226.771 kW), achieved a total energy recovery of 735.546 kW. Compared to the non-integrated base case, the implementation of heat integration strategies resulted in remarkable energy efficiency improvements: 31% reduction in heating utility consumption (from 734.546 kW to 509.898 kW), 37% reduction in cooling utility consumption (from 734.546 kW to 440.218 kW), and an overall external utility reduction of 35.3% (from 1,469.092 kW to 950.1164 kW), representing total energy savings of 518.9756 kW. These findings demonstrate that Pinch Technology provides a thermodynamically rigorous framework for achieving substantial energy savings in EDA production facilities, contributing to reduced operational costs, lower greenhouse gas emissions, and enhanced industrial sustainability.